Efficacy and safety of daptomycin versus linezolid treatment in patients with vancomycin-resistant enterococcal bacteraemia: An updated systematic review and meta-analysis. (June 2020) - Shi, Changcheng; Jin, Weizhong; Xie, Yaping; Zhou, Dongmei; Xu, Shuang; Li, Qingyu; Lin, Nengming
Highlights: Compared with linezolid treatment, daptomycin treatment showed comparable clinical and microbiological outcomes but a lower incidence of thrombocytopenia. High-dose daptomycin treatment should be considered for patients with VRE bacteraemia. More studies comparing diverse high-dose daptomycin and linezolid regimens are needed to determine if a proper high-dose regimen exists. Abstract: Objectives: A systematic review and meta-analysis were conducted to re-assess the efficacy and safety of daptomycin compared with linezolid treatment for vancomycin-resistant enterococcal (VRE) bacteraemia and to explore whether high-dose daptomycin is beneficial. Methods: PubMed, EMBASE, the Cochrane Library, and meeting abstracts were searched from inception to February 2019. Studies evaluating daptomycin and linezolid treatment for VRE bacteraemia were included. Results: Twenty-two observational studies were identified. A non-significant higher mortality (OR 1.27; 95% CI 0.99–1.63) and significantly lower risk of thrombocytopenia (OR 0.78; 95% CI 0.61–0.99) were found with daptomycin compared with linezolid treatment. Clinical response (OR 0.88; 95% CI 0.59–1.33), microbiological cure (OR 0.82; 95% CI 0.53–1.28), recurrence of bacteraemia (OR 0.96; 95% CI 0.70–1.32), and risk of creatine kinase elevation (OR 0.82; 95% CI 0.46–1.47) were similar for the two agents. In the subgroup analysis of studies focusing on high-dose daptomycin treatment, similar mortality was observed (OR 0.92; 95% CI 0.46–1.84). Moreover, patients receiving daptomycin tended to show a higher clinical response (OR 1.61; 95% CI 0.37–7.09) and microbiological cure (OR 2.09; 95% CI 0.43–10.1) and a lower risk of bacteraemia relapse (OR 0.47; 95% CI 0.15–1.45), although the difference was not significant. Conclusions: Compared with linezolid treatment, daptomycin treatment showed comparable clinical and microbiological outcomes but a lower incidence of thrombocytopenia. Because of the dose-dependent effect that was observed, high-dose daptomycin should be considered for patients with VRE bacteraemia.